Sistem Pakar Diagnosis Hama dan Penyakit pada Tanaman Bunga Sedap Malam dengan Dempster Shafer - Nindhy Prastiwi, Maulidina; Uky Yudatama, Uky; Agung Prabowo, Nugroho (Jurnal Komtika (Komputasi dan Informatika), 2019)
Nightly flower plants are one of the flower plants that are much in demand by the public. However, as time goes by the production of savory flower plants determines which one of the causes is caused by pests and diseases. Introduction of pests and diseases and its control sometimes not all farmers know it. This research develops an expert system that can help farmers diagnose pests and diseases that attack night flowering plants with the Dempster Shafer method. The results of this study are the application of an expert system that uses pests and tuberose flower diseases. This system will issue this edition to the publication of night flower pests and diseases inputted by users. The amount of this trust value is the result of calculations using the Dempster Shafer method. The conclusion in this study is that an expert system using the Dempster Shafer method for approval to release pests and diseases of the nightly flower plants is very helpful in overcoming the problem of improving the quality of the nightly flower production.